Interação entre bactérias diazotróficas e doses de n-fertilizante na cultura da cana-de-açúcar - Oliver, Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sugarcane is a highly extractive culture in nitrogen. Besides the high cost of nitrogen fertilizers, these have low agronomic performance causing major environmental impacts. An economical alternative and environmentally advantageous to reduce the use of nitrogen fertilizer would be to increase biological nitrogen fixation by inoculation with diazotrophic bacteria. In this context, the present study aimed to verify the effect of inoculant formed by diazotrophic bacteria associated with different N-fertilizer doses applied in two ways, in increasing the efficiency of nitrogen use, with possible increase in productivity sugarcane with reduced mineral N source. The field experiment was conducted in the city of Igaraçu do Tietê/SP during the crop season 2011/2012. The variety RB92579 was used in the first ratoon cycle in a production environment classified as A. The treatments consisted of different N doses (0, 60, 90 and 120 kg ha-1) associated or not with a mixed of five diazotrophic bacteria species (inoculant) in two inoculation methods (injected immediately after cutting the clumps and foliar application 60 days after cutting the clumps). The inoculum used was a strains mixed of five isolated bacteria species from sugarcane (Gluconacetobacter diazotrophicus, Herbaspirillum seropedicae, Herbaspirillum rubrisubalbicans, Azospirillum amazonense e Burkholderia tropica). The Nitrogen doses were applied at 60 days after sprouting sugarcane ratoon. The experimental design was a randomized block in a 4x3 factorial scheme, constituted by nitrogen doses (N) and management of inoculation (M) totaling 12 treatments with four replicates. The number of failures and the nitrogen content in the leaves were determined at 120 days after initiation of shoots. At harvest physiological assessments (SPAD index and chlorophyll content), number of tillers, biometrics (length and diameter of stalk), technological analysis (theoretical recoverable sugar ...

A cana-de-açúcar é uma cultura altamente extrativa em nitrogênio. Além do alto custo dos fertilizantes nitrogenados, esses apresentam baixo aproveitamento agronômico causando grandes impactos ao ambiente. Uma alternativa econômica e ambientalmente vantajosa para reduzir o uso da adubação nitrogenada seria o aumento da fixação biológica do nitrogênio pela inoculação com bactérias diazotróficas. Diante desse contexto, o presente trabalho teve como objetivo verificar o efeito de inoculante, formado por bactérias diazotróficas, associado a diferentes doses de N-fertilizante, aplicados em duas maneiras, no aumento da eficiência de utilização de nitrogênio, com possível elevação da produtividade de cana-de-açúcar com redução de fonte de N mineral. O ensaio de campo foi desenvolvido na região do município de Igaraçu do Tietê/SP durante o ano agrícola de 2011/2012. Foi utilizada a variedade RB92579, no ciclo de cana-soca de primeiro corte, em ambiente de produção classificado como A. Os tratamentos foram constituídos por diferentes doses de N (0, 60, 90 e 120 kg ha-1) associadas ou não a uma mistura de cinco espécies de bactérias diazotróficas (inoculante) em dois métodos de inoculação (aplicação injetada logo após o corte das touceiras e aplicação foliar após 60 dias do corte das touceiras). O inoculante utilizado foi uma mistura de estirpes de cinco espécies de bactérias isoladas da cana-de-açúcar (Gluconacetobacter diazotrophicus, Herbaspirillum seropedicae, Herbaspirillum rubrisubalbicans, Azospirillum amazonense e Burkholderia tropica). As doses de nitrogênio foram aplicadas aos 60 dias após a brotação da cana-soca. O delineamento estatístico foi em blocos ao acaso, em esquema fatorial 4x3, constituindo-se dos fatores doses de nitrogênio (N) e manejos da inoculação (M) totalizando 12 tratamentos, com quatro repetições. Foram determinados aos 120 dias após inicio das brotações ...
Keywords: Cana-de-açúcar - Inoculação; Plantas - Efeito do nitrogenio; Nitrogenio - Fixação; Microorganismos fixadores de nitrogenio; Sugar-cane